The emergence of Kurdish studies in Russia in the middle of the nineteenth century - Mustafa, Aram Ali (Sulaimani Journal for Humanities, 2019)
After the Russian Empire had chosen to intervene in the Great Powers’ conflicts in the Middle East where dramatic changes in its political landscape were underway, they thus shifted their approach to extend direct control over vast areas to south-west Asia, aiming to reach the Caucasus and the regions beyond to further impose their hegemony. However, Iran and the Ottoman Empire were the major barriers to Russian expansion at that time, and they were being at wars with Russia respectively. Most of these battles happened on the Kurdish lands, and they, as residents of the area, even made significant parts of the Ottoman and Iran’s armies in the wars against Russia. The Russians were initially doubtful of the Kurds and did not give them much attention. However, when the Kurds’ significance in the political equations was evident, the Russians started to engage with the Kurds aiming to secure their alliance. To achieve this, all possible means were used by the Russians, namely through their diplomats and government representatives. In this regard, the Russians officials had to acquire information about various aspects of the Kurds, including but not limited to, their language, literature, history, mythology, tradition, religious beliefs and even an understanding of their psychology. It was during this period when people like Peter Lerch and Alexandre Jaba were asked by the Russian Academy of Sciences to start studying the Kurds and collecting data on them. This paper examines the circumstances leading to the Russian engagement with the Kurds, which was first initiated by the Russian diplomats and other political/military officers based in the region. It, moreover, looks at the various factors behind Russia’s interest in the study of the Kurds, which was then developed as a basis of Kurdology; an established discipline as part of Russian Orientalism.